Unusual Cerebral Involvement of Rheumatoid Arthritis Mimicking a Tumor - Tokdemir, Sevil; TOKDEMİR, SEVİL; TOPRAK, HÜSEYİN; TOPRAK, HÜSEYİN; ALKAN, ALPAY; ALKAN, ALPAY (My University, 2020)
Background: The central nervous system-s involvement in Rheumatoid Arthritis (RA) is infrequent and can be life-threatening. Mass-like CNS involvement is an unusual presentation. A 45 year old man had suffered seropositive rheumatoid arthritis for five years referred to our hospital with one-week history of right-sided facial paralysis, left hemiparesis and headache.